al-Nizam al-qada'i fi wilayat Tarabulus al-gharb fi al-'ahd al-'Uthmani al-thani, 1835-1879 - al-Hazil,'Ali'Umar'Abd al-Rahman (Tarabulus, Libiya : al-Markaz al-Watani lil-Mahfuzat wa-al-Dirasat al-Tarikhiyah, 2009)
Judicial; laws and legislation; Libya; Ottoman era; history.
Includes bibliographical references (p. 302-319) and indexes.
Keywords: Justice, Administration of -- Libya -- Tarabulus (Province) -- History; Courts -- Libya -- Tarabulus (Province) -- History